SIZE REDUCTION OF KLOPFENSTEIN-BALUN TRANSFORMER FOR BALANCED ANTENNAS - P. Shastri, Shailendra; R. Singh, Ravish; Y. Pawar, Sandeep (Malaysian Journal of Science, 2021)
A BALUN transformer converts impedance into another one and also converts an unbalanced line into a balanced line. A compact size broadband BALUN transformer is designed using Klopfenstein taper line transformer approach to transform 50â„¦ impedance into 100 â„¦. The results of the conventional BALUN are compared with the proposed compact size BALUN. In order to reduce the length of the BALUN, a curved microstrip line is used. The proposed compact size BALUN is 56 %- 70 % smaller in size w.r.t the conventional BALUN but at the cost of 6% - 11% reduction in the overall band. The conventional BALUN has measured % bandwidth of 165 while the reduced size BALUN has 159. The measured results are in agreement with the simulated results.